Enhancing High-concentrated Wastewater Quality on Evaporation Rate from Five-Consecutive Oxidation Ponds as Located in Phetchaburi, Southerly Thailand - Maskulrath, Parkin; Bualert, Surat; Chunkao, Kasem; Jinjaruk, Thanawat; Pattamapitoon, Thanit; Wararam, Watcharapong; Szymanski, Wladyslaw W. (Applied Environmental Research, 2021)
This research aimed to examine the environmental factors determining the rates of evaporation, a natural phenomenon contributing to the treatment of wastewater of 5-consecutive oxidation ponds of the King’s Royally Initiated Laem Phak Bia Environmental Research and Development Project. Data collected from the 17th of April to 30th of May 2019 by US Class A Evaporation Pan revealed that the sedimentation pond (Pond 1) has the highest rate, 7.22 mm d-1, the oxidation pond 1 (Pond 2), 5.70 mm d-1, the oxidation pond 3 (Pond 4), 5.56 mm d-1, the stabilization pond (Pond 5), mm d-1, the reference pond at 5.07 mm d-1 and the oxidation pond 2 (Pond 3), 3.59 mm d-1. Concluding the evaporation in domestic wastewater treatment plants is characterized by 1) heat generated from short and long wave radiation emitted by earth and the sun, 2) local wind profiles of the area affected the height differences of the roughness length, and 3) heat generated by the respiration and digestion process of microbial activities and other grey body contaminants. Presenting the day and night variations made for the analysis, the day evaporation was significantly higher resulted by the net radiation were accountable. Wind profile generated from the measurement of speeds and directions at two different sites at 3 and 10 m has explained for the roughness length heights over each pond as lower roughness height have cause the increased in the rates of evaporation in Pond 4 and 5 however, these processes were also suppressed by high ionic bonding molecules effected suggested by the high TDS and EC values. The vertical temperature profile has conveyed the movement in the heat flux that dominated an upward flux movement in Pond 1. This is the exothermic reaction from the digestion process have suggested that extra heat has been added.